(untitled) (International relations and international law Journal, 2016)
The Caspian region is rich in large deposits of oil & gas that is attractive aspect of foreign interests and investments. Geopolitical component of the region attaches particular importance to the global chess game, primarily due to the proximity of the region to the world forces centers. These are the multinational companies extracting oil and gas that have tested the possible models of cooperation between the Caspian states. As long as there is a demand for mineral resources, there will always be an offer to trade them, leaving many problem areas in the relationship both between the Caspian states, and individual countries of Europe and EU as a whole. Being one of the world’s energy consumers, the Italian Republic represents the energy market by subsidiary of “Agip KCO BV ” the well-known holding company “ENI”, which has a significant position in the Caspian Sea, that contribute to the strengthening of strategic relationships with such countries and regions like Kazakhstan and Azerbaijan.